Swedish Twitter 2015 - Språkbanken Text (University of Gothenburg, 2024)
Material collected from a selection of Swedish speaking twitter users from 2015

Material från ett urval av svenskspråkiga Twitteranvändare från 2015
Svensk Twitter 2015
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik